TOURIST TEMPTATIONS AND THE ROLE OF RESPONSIBLE TOURISM IN ITS SUSTAINABILITY - Dr. Zainab Sadiq Mustafa (Scholar Express Journal, 2022)
Growth in tourism sector in any country faces many important challenges such as scarcity of natural resources, climate change, biodiversity vanish, The necessity of preserving of the environment and maintain its resources, in addition to the importance of maintaining a high level of quality of service provided in tourist destinations(TD). These challenges have led governments, international organizations, (TD) and non-governmental organizations to work together to adopt appropriate policies and approaches to achieve required balance among the economic, social , environmental objectives of (TD), the importance of adhering to principles and principles of sustainable , responsible tourism comes at forefront of this balance requirement. It is essential that a person understands that resources of this planet are limited , must be used and exploited rationally and equitably. This research deals with responsible tourism(RT) in terms of concept , characteristics as a modern tourist patterns , how it contributes to sustainability of tourist attractions in places of (TD)and how the tourist is a key player in this process with a look at some of the experiences of countries in this type of tourism
Keywords: Responsible tourism(; tourist attractions